1993
DOI: 10.1677/joe.0.1360017
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin receptor concentrations, inositol phosphate turnover and prostaglandin release by endometrium from ewes induced to ovulate during the early post-partum period

Abstract: Induction of ovulation early post partum in sheep is associated with a high incidence (30-40%) of premature luteolysis. The present study was designed to characterize oxytocin receptor levels, oxytocin-stimulated inositol phosphate (IP) turnover (second messenger) and oxytocin-stimulated prostaglandin F2 alpha (PGF2 alpha) release in the endometrium of post-partum ewes induced to ovulate 21 days after parturition and expected to exhibit a range of corpus luteal functions subsequently. Ovulation was induced on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Sharpe et al (1986) reported that corpora lutea obtained from post-partum ewes are lighter and have lower LH receptor populations than those obtained from cyclic ewes, while Wallace (1995) demonstrated a lower steroidogenic capacity in vitro. Restoration of functional integrity appears to take longer however as Fredriksson (1985) reported elevated circulating concentrations of 15keto-13,14-dihydro-PGF2oc, a metabolite of PGF2°=, for up to 28 days post partum and Wallace et al (1993) detected high concentrations of uterine oxytocin receptors, an integral part of the luteolytic mechanism, as late as day 35. Rubianes and Ungerfeld (1993) observed that, in autumn lambing Corriedale ewes, macroscopic uterine involution was completed by day 17 post partum.…”
Section: Discussionmentioning
confidence: 99%
“…Sharpe et al (1986) reported that corpora lutea obtained from post-partum ewes are lighter and have lower LH receptor populations than those obtained from cyclic ewes, while Wallace (1995) demonstrated a lower steroidogenic capacity in vitro. Restoration of functional integrity appears to take longer however as Fredriksson (1985) reported elevated circulating concentrations of 15keto-13,14-dihydro-PGF2oc, a metabolite of PGF2°=, for up to 28 days post partum and Wallace et al (1993) detected high concentrations of uterine oxytocin receptors, an integral part of the luteolytic mechanism, as late as day 35. Rubianes and Ungerfeld (1993) observed that, in autumn lambing Corriedale ewes, macroscopic uterine involution was completed by day 17 post partum.…”
Section: Discussionmentioning
confidence: 99%